2010
DOI: 10.1074/jbc.m110.131136
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed Amelogenin Secondary Structure Leads to Uncontrolled Aggregation in Amelogenesis Imperfecta Mutant Proteins

Abstract: Mutations in amelogenin sequence result in defective enamel, and the diverse group of genetically altered conditions is collectively known as amelogenesis imperfecta (AI). Despite numerous studies, the detailed molecular mechanism of defective enamel formation is still unknown. In this study, we have examined the biophysical properties of a recombinant murine amelogenin (rM180) and two point mutations identified from human DNA sequences in two cases of AI (T21I and P41T). At pH 5.8 and 25°C, wild type (WT) rM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…Note that it was necessary to perform the experiments at pH 5.5 and at lower TFE concentrations to be able to reliably measure the hydrodynamic radius of amelogenin monomers. 17,18,27 If the pH is too acidic, the positive charge on the surface of the monomers can cause accelerated diffusion due to charge-charge repulsion. 17,18,27 Similarly, we found that, despite thorough mixing, TFE content > 10% v/v increases light scattering and leads to errors in interpretation.…”
Section: Tfe Induces Rp172 Self-assembly At Low Phmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that it was necessary to perform the experiments at pH 5.5 and at lower TFE concentrations to be able to reliably measure the hydrodynamic radius of amelogenin monomers. 17,18,27 If the pH is too acidic, the positive charge on the surface of the monomers can cause accelerated diffusion due to charge-charge repulsion. 17,18,27 Similarly, we found that, despite thorough mixing, TFE content > 10% v/v increases light scattering and leads to errors in interpretation.…”
Section: Tfe Induces Rp172 Self-assembly At Low Phmentioning
confidence: 99%
“…17,18,27 If the pH is too acidic, the positive charge on the surface of the monomers can cause accelerated diffusion due to charge-charge repulsion. 17,18,27 Similarly, we found that, despite thorough mixing, TFE content > 10% v/v increases light scattering and leads to errors in interpretation. The introduction of 10% v/v TFE lead to an increase in the average hydrodynamic radius of rP172 (i.e., from 3.66 6 1.69 nm in the absence of TFE to 6.04 6 2.25 nm in the presence of 10% TFE).…”
Section: Tfe Induces Rp172 Self-assembly At Low Phmentioning
confidence: 99%
See 2 more Smart Citations
“…The mixtures were incubated for 20-30 min before measurements and data were analyzed as previously described [Moradian-Oldak et al, 2000;Fan et al, 2008, Laksminarayanan et al, 2010.…”
Section: Dynamic Light Scatteringmentioning
confidence: 99%